Attachment style, psychotic phenomena and the relationship with aggression: investigation in a general population sample - Whale, Katherine; Green, Kathleen; Browne, Kevin (Emerald, 2018)
Purpose: This study aimed to explore the relationship between attachment style, sub-clinical symptoms of psychosis and aggression in a general population sample. Design: Using both convenience and snowball sampling, participants in the community (n=213) completed an online questionnaire including previously validated measures of adult attachment, aggression and psychotic like events. Findings: Results suggested that there were statistically significant correlations between all study variables. Multiple linear regression demonstrated that total psychotic-like experiences and attachment scores significantly predicted variance in total aggression. Moderation approaches revealed that the relationship between psychotic-like events and aggression was stronger in individuals with more insecure attachment styles. Research limitations/implications: This generalisability of the results is compromised by the sampling methodology and the use of self-report tools. However, the significant results would support larger scale replications investigating similar variables. Originality/value: This study suggests there is a relationship between psychotic like experiences and facets of aggression in the general population. The findings suggest that attachment is a contributing factor to aggression associated with psychotic like experiences, and highlight the need for similar investigations within clinical samples. The results imply that attachment may be a useful construct for explanatory models of the relationship between adverse childhood experiences, psychotic experiences and aggression.